A New Cyte in Orthodontics: Osteocytes in Tooth Movement - Bumann, E. E. (Orthod Craniofac Res, 2017)
OBJECTIVES: Orthodontic tooth movement (OTM) relies on the orchestration of clinical and biologic events that include the application of clinical force followed by a cascade of cellular and molecular responses. Our understanding about OTM today has evolved from, and is largely based on historic studies. However, the advances in bone biology and clinical orthodontics today continue to pave the pathway toward an improved knowledge base, and state of the art therapeutics in OTM. Osteoblasts and osteoclasts have been the primary cells analyzed in OTM. However, the role of osteocytes, a cell previously thought to be static, should be considered in light of new findings in molecular biological research. Osteocytes are now known to be significant in controlling responses to mechanical forces and therefore may be central to both OTM and normal tooth eruption. In this review we explore the biology of OTM by focusing specifically on the potential role of osteocytes. CONCLUSION: Evidence from recent studies reveal that osteocytes have a role in controlling the response to mechanical forces and OTM. We therefore propose that these findings and further research endeavors may shape the future of clinical applications – specifically enhanced outcomes in OTM.